An experiment with serious games on mathematics in higher education - Descalço, L. (2022)
Using serious games in education can be beneficial by improving student’s motivation. It is not so clear if learning can be improved as a direct consequence of using serious games. Can students become good players without acquiring the learning outcomes established? Of course, it depends on the games and context. Hence, we are trying to understand the effect of a particular kind of games in a particular context on a mathematics course. Our context is calculus for second year students of sciences and engineering. Games were used in only one topic of the course: limits of vector functions. We compare results students have on the games with results in assessment tests and final examinations and with results in other topics. The games are, essentially, simple tests with multiple-choice questions about the topic. Students are ranked by the number of correct questions and time taken to complete the game. By including questions in assessment tests that are known from the games and others that are not we compare results with the goal of contributing to the answer to the following general question: are students really learning with serious games or just getting better in the games? We have 545 students in the calculus course, but we consider only 275 students from a particular subset of engineering courses that have participated in the assessment tests. All students in the course have available a computer platform, SIACUA, where multiple-choice questions are used as tool for learning. The focus is on the detailed solutions proposed for the questions. Students have access to these solutions after answering the question or even without providing an answer. Hence, we are in a context where multiple-choice questions are widely used, for learning, in assessment and in serious games. In the main assessment tests and final examination, all questions are open answer questions and there are no multiple-choice questions. We present the conclusion of this experiment and some considerations about teaching, learning, games and motivation in mathematics on higher education.